2014
DOI: 10.1111/aab.12155
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, identification and disease management of grape black rot and potentially useful metabolites of black rot pathogens for industrial applications – a review

Abstract: Phyllosticta ampelicida (teleomorph: Guignardia bidwellii) is the fungal plant pathogen that causes black rot on grapevine. It is able to infect all green, expanding grape tissues. Black rot poses a threat to both yield and wine quality; a severe attack can virtually cause a complete crop loss. The fungus is native to North America, and was spread to Europe at the end of the 19th century. With the beginning of the 21st century, an increasing importance of the disease was observed in several European winegrowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
(97 reference statements)
0
19
0
Order By: Relevance
“…Since studies of Loskill et al (2009) demonstrated that spores (conidia or ascospores) are produced throughout the growing season in the overwintering mummies, VitiMeteo Black rot assumes sufficient inoculum to be present throughout the season (in regions or vineyards with black rot symptoms in the previous or the present year). Since conidia are responsible for the rapid spread of the disease in the field (Ferrin and Ramsdell 1978), they are considered as major source of infections during summer (Molitor and Beyer 2014).…”
Section: Model Performancementioning
confidence: 99%
See 3 more Smart Citations
“…Since studies of Loskill et al (2009) demonstrated that spores (conidia or ascospores) are produced throughout the growing season in the overwintering mummies, VitiMeteo Black rot assumes sufficient inoculum to be present throughout the season (in regions or vineyards with black rot symptoms in the previous or the present year). Since conidia are responsible for the rapid spread of the disease in the field (Ferrin and Ramsdell 1978), they are considered as major source of infections during summer (Molitor and Beyer 2014).…”
Section: Model Performancementioning
confidence: 99%
“…Black rot lesions on leaves reduce assimilation and form the inoculum for further infections during the season while most severe damage is caused by cluster infections. From an economic point of view, almost no black rot damage on the clusters can be tolerated (Molitor and Beyer 2014).…”
Section: Model Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The secondary metabolites are believed to be involved in the pathogenicity of G. bidwellii and can be described as potential virulence factors, due to the fact that the application of the pure compounds onto the host tissue causes specific disease symptoms 6 . Additional studies should be conducted to corroborate this hypothesis.…”
Section: Introductionmentioning
confidence: 99%